The Toronto Western Spasmodic Torticollis Rating Scale: Reliability in neurologists and physiotherapists - Boyce, Melani J.; Canning, Colleen G.; Mahant, Neil; Morris, John; Latimer, Jane; Fung, Victor S.C. (Parkinsonism & related disorders, 2012)
Inter-rater reliability for the Toronto Western Spasmodic Torticollis Rating Scale has been determined for neurologists, but not for physiotherapists. We assessed the inter-rater reliability of scoring the clinical severity subscale of the Toronto Western Spasmodic Torticollis Rating Scale by two physiotherapists and two neurologists. Seven individuals with cervical dystonia were assessed on video a total of 23 times. The assessments were randomized and rated by all raters. Reliability for all raters considered together, assessed by the Intraclass Correlation Coefficient (ICC 2,1) was 0.74 (p < 0.001, 95% CI 0.46–0.88). Reliability for the two clinician groups was not significantly different: neurologists ICC (2,1) = 0.75 (p < 0.001, 95% CI 0.44–0.89), physiotherapists ICC (2,1) = 0.82 (p < 0.001, 95% CI 0.30–0.94). The clinical severity subscale of the Toronto Western Spasmodic Torticollis Rating Scale can be assessed with good inter-rater reliability when physiotherapists and neurologists are represented in the same rater pool.